2014
DOI: 10.1124/dmd.114.058719
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Pharmacokinetics in Rats Is Altered as a Function of Age, Impacting the Interpretation of Animal Model Data

Abstract: Several behavioral studies report that adolescent rats display a preference for nicotine compared with adults. However, age-related pharmacokinetic differences may confound the interpretation of these findings. Thus, differences in pharmacokinetic analyses of nicotine were investigated. Nicotine was administered via acute s.c. (1.0 mg base/kg) or i.v. (0.2 mg base/kg) injection to early adolescent (EA; postnatal day 25) and adult (AD; postnatal day 71) male Wistar rats. Nicotine and its primary metabolite, cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 51 publications
6
37
1
Order By: Relevance
“…Studies examining SA at higher unit nicotine doses that maintain less robust SA, presumably due to aversive or other side effects (e.g., 0.09 mg/kg/infusion), might help clarify this issue. On the other hand, the serum nicotine concentrations produced by the 1.0–1.25 mg/kg nicotine doses in the ICSS study may be higher than what most rats could achieve with higher NSA unit doses (Craig et al, 2014; Donny et al, 2000; LeSage et al, 2002). If so, the ICSS findings may reflect an attenuation of nicotine’s toxic effects rather than its abuse liability.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Studies examining SA at higher unit nicotine doses that maintain less robust SA, presumably due to aversive or other side effects (e.g., 0.09 mg/kg/infusion), might help clarify this issue. On the other hand, the serum nicotine concentrations produced by the 1.0–1.25 mg/kg nicotine doses in the ICSS study may be higher than what most rats could achieve with higher NSA unit doses (Craig et al, 2014; Donny et al, 2000; LeSage et al, 2002). If so, the ICSS findings may reflect an attenuation of nicotine’s toxic effects rather than its abuse liability.…”
Section: Discussionmentioning
confidence: 75%
“…Second, it is unclear to what extent the relative blood levels of nicotine and non-nicotine constituents in rats in the present study are comparable to what occurs in EC users. The lower doses used in the ICSS model and the unit dose used in the SA model yield blood nicotine concentrations in the range of smokers or EC users (Benowitz et al, 1982; Craig et al, 2014; Farsalinos et al, 2015; LeSage et al, 2002). Therefore, to the extent that relative concentration of key constituents in blood is similar to that in EC aerosol, levels of non-nicotine constituents in our model would be comparable to that in humans.…”
Section: Discussionmentioning
confidence: 99%
“…For plasma quantification, 100 μl plasma samples were prepared as previously described (Craig et al , 2014; Vieira-Brock et al , 2013). The prepared dialysate and plasma samples were then analyzed by LC-MS as previously described (Craig et al , 2014). Cotinine dialysate levels were near and at the limit of detection; thus, cotinine levels were not reliably quantifiable.…”
Section: Methodsmentioning
confidence: 99%
“…One possibility is that age differences in pharmacokinetics could account for reduced sensitivity to METH in adolescents, but findings are again mixed. Studies examining plasma and brain levels of stimulants have found that adolescents have lower (Spear and Brake 1983;Kokoshka et al 2000;McCarthy et al 2004;Craig et al 2014), higher (Caster et al, 2005), or similar levels (McCarthy et al, 2004;Caster et al, 2005) compared to adults. Based on the extensive changes occurring in the brain during adolescence (Andersen et al 1997(Andersen et al , 2000Dagher et al 2001;Koss et al 2014;Juraska and Willing 2017), another possibility is that differences in pharmacodynamics (e.g.…”
Section: Discussionmentioning
confidence: 99%